Effect of the essential volatile oils isolated from Thymbra capitata (L.) Cav. on olive and sunflower oils - Miguel, Maria Graça (2015)
The chemical composition of the volatile constituents of the oils isolated from different parts of Thymbra capitata collected at different developmental stages were analysed by GC and GC/MS. The antioxidant ability of the oils isolated from T capitata was evaluated determining the peroxide values, on olive and sunflower oils, stored at 60 degreesC. These peroxide values were compared with those obtained when BHT, carvacrol and control (without adding antioxidants) were used and subjected to the same conditions. The best yield oil was obtained from the whole aerial part of T capitata collected during the flowering phase. The major component of the oils was carvacrol. Relative high amounts of p-cymene, gamma-terpinene and beta-caryophyllene were also found. BHT revealed to be the best antioxidant when the olive oil was used. On sunflower oil, the antioxidant ability of BHT was not so evident, being the carvacrol-rich essential oils of T capitata or carvacrol more important antioxidants.